Clinical application of confocal laser endomicroscopy in the diagnosis of malignant pleural effusion - Ye, Shenglan; Yuan, Mingli; Song, Cheng; Yang, Zhen; Hu, Yi; Ni, Jixiang (Frontiers in Oncology, 2026)
ObjectiveProbe-based confocal laser endomicroscopy (pCLE) is an innovative in vivo microscopic imaging technique that enables real-time visualization of tissue cytology during endoscopic examinations. This study aimed to evaluate the clinical utility of pCLE in diagnosing MPE.MethodsA total of 41 patients with pleural effusion (PE) who underwent pCLE examination were enrolled in this prospective study. The diagnostic performance of pCLE was assessed by calculating sensitivity (SEN), specificity (SPE), positive predictive value (PPV), negative predictive value (NPV), and accuracy (ACC), using histopathological results as the reference standard. Additionally, the safety profile of the pCLE procedure was evaluated.ResultsAmong the 41 patients, histopathological analysis confirmed MPE in 31 patients and benign pleural effusion (BPE) in 10 patients. Of the 31 MPE cases, 26 were lung adenocarcinoma (LUAD), 2 were lung squamous cell carcinoma (LSCC), 1 was large cell lung cancer (LCLC, a subtype of non-small cell lung cancer [NSCLC]), 1 was pleural malignant mesothelioma (PMM), and 1 was pleural metastasis from other tumors. Compared with histopathology, pCLE demonstrated a sensitivity of 96.77%, specificity of 80%, accuracy of 92.68%, PPV of 93.75%, and NPV of 88.89%. There was substantial agreement between pCLE and histopathological findings (kappa = 0.79, p < 0.001). Furthermore, compared to conventional thoracoscopy, pCLE facilitated targeted biopsy sampling and improved detection of malignant lesions. No adverse events related to pCLE were observed, indicating its favorable safety profile.ConclusionsOur study demonstrates that pCLE is a valuable tool for enhancing the diagnosis of MPE, with high concordance with histopathological findings (kappa = 0.79, p < 0.001) and significant guidance for thoracoscopic pleural biopsies. The diagnostic sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of pCLE were 96.77%, 80%, 92.68%, 93.75%, and 88.89%, respectively, when compared with histopathology. These results indicate that pCLE can effectively differentiate between benign and malignant pleural effusion in patients with undetermined etiology and serves as a robust complementary method to existing diagnostic approaches. However, the small sample size of this study limits the generalizability of the findings, and further large-scale, multicenter clinical trials are needed to validate these results.